2017
DOI: 10.1074/jbc.m117.795591
|View full text |Cite
|
Sign up to set email alerts
|

The hnRNP RALY regulates transcription and cell proliferation by modulating the expression of specific factors including the proliferation marker E2F1

Abstract: The heterogeneous nuclear ribonucleoproteins (hnRNP) form a large family of RNA-binding proteins that exert numerous functions in RNA metabolism. RALY is a member of the hnRNP family that binds poly-U-rich elements within several RNAs and regulates the expression of specific transcripts. RALY is up-regulated in different types of cancer, and its down-regulation impairs cell cycle progression. However, the RALY's role in regulating RNA levels remains elusive. Here, we show that numerous genes coding for factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 82 publications
1
32
0
Order By: Relevance
“…RALY belongs to the heterogeneous nuclear ribonucleoprotein family that binds to poly-U elements within several RNAs (64,65). It has been recently shown that RALY is able to stabilize E2F1 mRNA by binding to its 3′-UTR (48). Here, we identify EMS as a RALY binding partner.…”
Section: Ems Exerts Its Oncogenic Role By Increasing E2f1 Expressionmentioning
confidence: 83%
See 1 more Smart Citation
“…RALY belongs to the heterogeneous nuclear ribonucleoprotein family that binds to poly-U elements within several RNAs (64,65). It has been recently shown that RALY is able to stabilize E2F1 mRNA by binding to its 3′-UTR (48). Here, we identify EMS as a RALY binding partner.…”
Section: Ems Exerts Its Oncogenic Role By Increasing E2f1 Expressionmentioning
confidence: 83%
“…Because many lncRNAs exert their functions through interaction with their target proteins (47), we hypothesized that EMS could regulate E2F1 mRNA stability in a similar manner. It has been recently shown that the heterogeneous nuclear ribonucleoprotein RALY, a poly-U binding protein, is able to stabilize E2F1 mRNA by binding to its 3′-untranscribed region (UTR) (48). Analysis of the EMS sequence revealed that EMS contains a poly-U stretch with 22 uridines (SI Appendix, Fig.…”
Section: Ems Exerts Its Oncogenic Role By Increasing E2f1 Expressionmentioning
confidence: 99%
“…Namely, hnRNP LL was observed to interact with the single‐stranded DNA i‐motif of the BLC2 promoter sequence to stimulate transcription in a DNA conformation‐dependent manner . In HeLa cells, hnRNP RALY can bind chromatin, via both RNA‐dependent and independent mechanisms, to regulate cell cycle signatures and proliferation . Moreover, the purine‐rich element binding protein (Pur) family is a highly conserved group of proteins with a variety of functions, including regulation of RNA transport and translation, and transcriptional regulation of genes including MYC through binding and remodeling of single stranded DNA .…”
Section: Single‐stranded Dna Binding Proteins Also Have Roles In Rna mentioning
confidence: 99%
“…[119] In HeLa cells, hnRNP RALY can bind chromatin, via both RNA-dependent and independent mechanisms, to regulate cell cycle signatures and proliferation. [120] Moreover, the purine-rich element binding protein (Pur) family is a highly conserved group of proteins with a variety of functions, including regulation of RNA transport and translation, and transcriptional regulation of genes including MYC through binding and remodeling of single stranded DNA. [121][122][123][124] In Drosophila, regulation of MYC transcription by the RNA-binding protein B52 has been reported, [125] although it is unclear whether this occurs as a result of direct interaction with single-stranded DNA in the promoter.…”
Section: Single-stranded Dna Binding Proteins Also Have Roles In Rna mentioning
confidence: 99%
“…RALY is a member of the heterogeneous nuclear ribo-nucleoprotein family that binds poly-U-rich elements within several RNAs and regulates the expression of specific transcripts. Previous studies have shown that RALY is upregulated in different types of cancer, 6 8 , 19 and its downregulation impairs cell cycle progression. 19 A recent study demonstrated that RALY can promote invasiveness in breast cancer cells; additionally, RALY expression is increased in breast tumors, which correlates with decreased patient survival.…”
Section: Discussionmentioning
confidence: 97%